Plantar Purpura as the Initial Presentation of Viridians Streptococcal Shock Syndrome Secondary to Streptococcus gordonii Bacteremia. (17th April 2016) - Liao, Chen-Yi; Su, Kuan-Jen; Lin, Cheng-Hui; Huang, Shu-Fang; Chin, Hsien-Kuo; Chang, Chin-Wen; Kuo, Wu-Hsien; Ben, Ren-Jy; Yeh, Yen-Cheng
Abstract : Viridians streptococcal shock syndrome is a subtype of toxic shock syndrome. Frequently, the diagnosis is missed initially because the clinical features are nonspecific. However, it is a rapidly progressive disease, manifested by hypotension, rash, palmar desquamation, and acute respiratory distress syndrome within a short period. The disease course is generally fulminant and rarely presents initially as a purpura over the plantar region. We present a case of a 54-year-old female hospital worker diagnosed with viridians streptococcal shock syndrome caused by Streptococcus gordonii . Despite aggressive antibiotic treatment, fluid hydration, and use of inotropes and extracorporeal membrane oxygenation, the patient succumbed to the disease. Early diagnosis of the potentially fatal disease followed by a prompt antibiotic regimen and appropriate use of steroids are cornerstones in the management of this disease to reduce the risk of high morbidity and mortality.